ANALISIS FENOMENA JANUARY EFFECT PADA INDEKS KOMPAS100 DI BURSA EFEK INDONESIA - Ratu Lutfia, (2021)
The purpose of this research is to look at the anomalous market phenomenon that occurs in the Kompas100 index precisely located in the IDX. This phenomenon is an event where every January the average stock increases and can be called the January effect. Abnormal return and TVA are the selected variables. The objects taken are 74 companies in the IDX. The Sampling method is by looking at stocks that continuously appear in the period December 2017-January 2020. Hypothetical test used is different test Paired Sample t-test & Wilcoxon Sign Test. The results of this study state that there is a January effect phenomenon and there is a difference between abnormal return and TVA in January compared to other months in kompas100 index in IDX.